The Endgame or a Wake?: Tropes of Circularity in Literature Then and Now. Issue 2 (August 2016) - Marques, Diogo
Abstract : This paper argues that attending to the tropes of circularity featuring in print-based literature proves to be a useful foil for an analysis of electronic literature. Based on the idea that digital literary mechanisms do not obliviate previous circularity-inducing structuring motifs in analog literature, such as labyrinths, chess, rivers, and clockwork, this argument arrives at a crucial time for literature, which is currently the object of intensified debates on beginnings and ends, especially in the context of digitality and multisensory perception becoming central to some aspects of its processes. Accordingly, circular motion is here analysed in its depiction and actuation across several kinds of literary / literal machines, in reflection also on how sensory perception both mediate and is mediated. If literature is conditional upon a series of unique, though interconnected, mechanisms, it seems reasonable not to discard a certain circularity of the senses that is brought into play there and, indeed, given both thematic and formal substance in analog and digital works. In other words, representations generated at the confluence of both biological and technological bodies cannot but instigate a circularity on which they are dependent: an idea which this article examines and critiques with reference to canonical and electronic literature, particularly Borges, Beckett, and Joyce.